CD117 expression on blast cells in acute myeloid leukemia. - N. V. Goryainova; A. I. Gordienko; V. A. Kubarova (Medičnì Perspektivi)
The aim of the present work was to analyze the frequency of CD117 (c-KIT) antigen expression on the blast cells in acute myeloid leukemia (AML), evaluation of the presence of the relationship between the expression of the c-KIT and leukemia according to the FAB classification and definition of co-expression of the antigen CD117, antigens CD33 and CD34. The data of 47 patients with AML were diagnosed. M0 AML variant was established in 3 (6%) patients, M1 – in 2 (4%), M2 – in 9 (20%), M4 – in 22 (47%) and M5 – in 11 (23%). For immunophenotypic studies monoclonal antibodies (mAb) that detect antigens of anti-CD34, anti-CD33 and anti-CD117 (Becton Dickinson, USA) were used. The presence of the antigen CD117 was detected in 39 people, accounting for 83% of all surveyed. Antigen c-KIT was present in 48.1±17.0% cells on average: in all 3 cases – AML M0, in2 cases of AML M1, in 6 cases – AML  M2, 20 of 22 cases – AML M4 and in 8 of 11 AML M5 cases. Average levels of CD117 in investigated leukemia cases statistically differed significantly (p=0.0067).  Among 39 CD117- positive patients in 25 (53%) co-expression of CD117+/CD34+ was revealed. Expression of CD117+/CD34- was observed in 14 cases (30%), CD117-/CD34+ – in 4 cases (8,5%), CD117-/CD34- – in 4 cases (8.5%). CD34 had of 64% of cells of myeloid origin. A high positive correlation between expression of CD117 and CD34 (r=+0,5169) was determined, being statistically significant (p<0.0067). CD33 antigen was present on 81% of the studied cells. A weak negative correlation between expression of CD117 and CD33 (r=-0,2247), was revealed, being statistically significant (p>0,0067).